Serum thymidine kinase 1 levels correlates with FDG uptake and prognosis in patients with non small cell lung cancer - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2013)
Context: TK1 found to be elevated biomarker in many solid cancers. Objectives: The study aimed to assess the prognostic significance of a serum TK1 in patients with metastatic NSCLC. Methods: The study included 48 consecutive patients, newly diagnosed with metastatic NSCLC, and 10 healthy volunteers. Serum TK1 activity determined by ELISA method. Results: Patients with a bTK1 level > 156 Du L-1 had significantly shorter survival. TK1 level showed a strong correlation with primary tumor SUVmax. Discussion and conclusion: The magnitude of maximum fluorodeoxyglucose uptake in primary tumors and the serum TK1 level in patients with metastatic NSCLC were found to be independent prognostic predictors of overall survival.
Keywords: Thymidine kinase 1(TK1); non small cell lung cancer; DG uptake; prognosis; BREAST-CANCER; MARKER; PROLIFERATION; ASSOCIATION; DEGRADATION; RECURRENCE; LYMPHOMA; SURGERY; RISK